Factors associated with vaccination against Influenza A (H1N1) in the elderly - Victor,Janaína Fonseca (2014)
This study aimed to investigate the sociodemographic, clinical and behavioral factors and receiving information about the vaccine against pandemic influenza A (H1N1) associated with vaccination of elderly people. Study of quantitative and transversal nature, in which 286 elderly residents in Fortaleza, CE, Brazil participated. The association between variables was analyzed by the Pearson chi-square test, considering a 95% confidence interval and significance level (p≤0.05). The results revealed that, unlike the sociodemographic characteristics, many clinical, behavioral and informational aspects correlated significantly with adherence to Influenza A (H1N1) vaccination. It is believed that the findings can be used in strategies to control and prevent infection by viral subtypes within the elderly population, extensible even to other vaccine-preventable diseases, especially in light of possible future pandemics.